Selective Oxidation Depression of Copper-Activated Sphalerite by H2O2 During Chalcopyrite Flotation - Peiqiang Fan; Xiong Tong; Xian Xie; Qiang Song; Yuanlin Ma; Bin Han; Haitao Fu; Zhiming Lu (Metals)
Using hydrogen peroxide (H2O2), a simple and easily accessible reagent, as a selective depressant, flotation separation experiments of chalcopyrite and copper-activated sphalerite were conducted. The micro-flotation tests of single minerals indicated that H2O2 selectively depresses copper-activated sphalerite and exerted almost no depressant effect on chalcopyrite. In the flotation tests of artificially mixed minerals, a copper concentrate with a grade of 29.95% and a recovery of 87.30% was obtained, while the zinc content was only 5.76%, demonstrating a significant separation effect. The results of contact angle measurement, Zeta potential measurement, surface adsorption analysis, and XPS analysis suggested that H2O2 had a stronger oxidation capacity on the surface of copper-activated sphalerite than chalcopyrite, generating hydrophilic hydroxyl groups on the surface of sphalerite and preventing further adsorption of the collector Z-200 on the surface of sphalerite.